KERJASAMA PEMERINTAH RI-UNICEF DALAM MENDUKUNG RANCANGAN AKSI PERCEPATAN PEMBANGUNAN DI PAPUA (RAPPP) BIDANG PENDIDIKAN 2022-2024 - Mantiri, Romelyn; Seba, Roberto Octavianus Cornelis; Nau, Novriest Umbu Walangara (STIA Bina Banua Banjarmasin, 2024)
This research aims to analyze the collaboration between the government of the Republic of Indonesia (RI) and UNICEF in efforts to improve the education sector in Papua Province. Papua is one region that faces significant challenges in terms of access and quality of education. One form of the Government's attention in accelerating development in Papua is the ratification of Presidential Decree No. 24 of 2023 concerning the Master Plan for the Acceleration of Development for Papua (RIPPP) for 2022-2041 which is explained into 5 stages of the Papua Development Acceleration Action Plan (RAPPP). This research also evaluates the impact of this collaboration on increasing participation, availability of facilities, and quality of teaching in schools in Papua. The research results show that the collaboration between the Indonesian government and UNICEF has made a positive contribution to the development of the education sector in Papua. Some of the achievements include increasing school access, increasing the availability of educational facilities, and improving the quality of teaching. However, there are still challenges that need to be overcome to achieve more optimal results. This research provides in-depth insight into the importance of collaboration between governments and international institutions such as UNICEF in improving education in regions facing special challenges. Policy implications and recommendations for future development are also discussed in this research to provide guidance for related parties.